2019
DOI: 10.28982/josam.519328
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of concordance between referral diagnosis and electroneuromyographic diagnosis

Abstract: Aim: Electroneuromyography (ENMG) is an electrophysiological method of examination for neurophysiological state of motor neuron, peripheral nerve and muscle functions. This study was aimed to investigate the concordance of between referral diagnosis and ENMG diagnosis in patients referred to the electrophysiology laboratory. Methods: A retrospective cohort study is planned. Patients, whose evaluations of ENMG were requested by the orthopedic, neurology and physical therapy and rehabilitation physicians between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…ENMG plays an important role in medicine, especially to detect abnormalities in the muscle and neuromuscular junction. This device is useful in evaluating the neurophysiological condition of the motoric nerves, peripheral nerves, and the muscle function [1]. It has been shown that ENMG plays role in detecting the muscle activity in the patients with chronic respiratory disease [2], evaluating the respiration pattern of newborn baby, predicting the lung function of the children with asthma [3], detecting speaking ability in deaf people [4], and fatigue analysis [5].…”
Section: Introductionmentioning
confidence: 99%
“…ENMG plays an important role in medicine, especially to detect abnormalities in the muscle and neuromuscular junction. This device is useful in evaluating the neurophysiological condition of the motoric nerves, peripheral nerves, and the muscle function [1]. It has been shown that ENMG plays role in detecting the muscle activity in the patients with chronic respiratory disease [2], evaluating the respiration pattern of newborn baby, predicting the lung function of the children with asthma [3], detecting speaking ability in deaf people [4], and fatigue analysis [5].…”
Section: Introductionmentioning
confidence: 99%